The capability maturity model analysis of public health Centers in surabaya, Indonesia (Funded Work) - TJIPTO RINI (International Journal of Pharma and Bio Sciences, 2018)
Health-care is one of the several services provided by the Indonesian government. Most notable is the public health service whose main purpose is to increase the health as well as to prevent diseases among the population. The development of public health centers (Puskemas-Indonesian) or hospitals are considered necessary, especially when it is related to the variety of customer needs. In addition, it is deemed important to assess the maturity level of public health centers as an organization. The assessments are related to strategies, resources, and the management process in giving services. The main objective of this research was to determine their capability maturity model and to achieve the mission of pursuing a healthier life for all Indonesians. In order to do the research, 24 public health centers were chosen for evaluation. The Descriptive-cross sectional design was followed in the study. Results of the study showed that the level of maturity over 24 public health centers consisted of repeatable processes. Disciplinary processes were often found to be insufficiently rigorous; however, when applied, it showed to quality maintenance during times of stress. As such, the result of this research showed that maturity level of the organizations were at level two, which is the capability maturity model of public health centers in Surabaya, Indonesia were at a repeatable level.